Sustainability through Frugal Innovations : An Application of Indian Spiritual Wisdom - P., Avinash Shivdas; Chandrasekhar, J. (Prabandhan: Indian Journal of Management, 2016)
Today, the entire world is on the brink of disaster. The waves of crises like global warming, climate change, financial crisis, mental traumas, and tensions are engulfing mankind. Many business strategies are being discussed with sustainability as the watch word. In this context, the age-old Indian wisdom has much to offer. The gap between the haves and have-nots is on the rise. Affordability of many products is becoming a distant dream for the common man. To cater to the needs and wants of the contemporary world, firms have to adopt frugal innovation to produce low-cost and high-quality sustainable products/services. The aim of this paper was to create a conceptual model of understanding sustainability through frugal innovation by combining ideas from these fields and basing the model on the spiritualistic perspective of Indian wisdom. The case study methodology was adopted to substantiate the above conceptual model.